2020
DOI: 10.3122/jabfm.2020.06.190454
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Understanding of the Relationship Between Their Diabetes and Periodontal Disease

Abstract: Introduction: There is a paucity of research on awareness, education, and interventions that address increased risk of developing periodontal disease, the sixth complication of diabetes. Examining the knowledge of patients with diabetes and understanding of the bidirectional relationship between periodontal disease and diabetes could inform future diabetes self-management care. We assessed the knowledge and understanding of the bidirectional relationship between diabetes and periodontal disease; examined gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…In addition, a total of seven studies were included by manual search. Finally, 24 studies 27–50 were included in the qualitative synthesis. Some studies that initially appear to meet the inclusion criteria were later excluded due to different reasons as follows: did not evaluate the bidirectional relationship (15), or did not include people with diabetes (3) and based on exclusion criteria (study design) (3) were excluded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a total of seven studies were included by manual search. Finally, 24 studies 27–50 were included in the qualitative synthesis. Some studies that initially appear to meet the inclusion criteria were later excluded due to different reasons as follows: did not evaluate the bidirectional relationship (15), or did not include people with diabetes (3) and based on exclusion criteria (study design) (3) were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the 24 included studies are outlined in Table 2. All included studies used a cross‐sectional design 27–50 . A total of 8693 patients were evaluated in all included studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many people reported that they managed their oral health through various self-care oral hygiene practices, primarily through toothbrushing. While most individuals across the review brushed their teeth once daily, toothbrushing twice daily was low compared to populations with diabetes in other regions, such as in Australia [ 61 ], Italy [ 64 ] and USA [ 65 ]. Banyai et al [ 66 ] collected information about oral health behaviours among people with diabetes across 60 countries, with half of respondents originating from Europe and none from South Asia.…”
Section: Discussionmentioning
confidence: 99%
“…A remote diabetes screening exercise was developed and conducted during the 2020 fall semester using an asynchronous online learning system 2 . This asynchronous learning exercise included a new training video and a prerecorded lecture emphasizing the bidirectional relationship between oral health and diabetes 3 . The newly developed training video provided a detailed demonstration of the proper use of a glucometer.…”
Section: Solutionmentioning
confidence: 99%